A content analysis of propaganda in Harakah newspaper / Shamsiah Abd Kadir and Ahmad Sauffiyan Abu Hasan - Abd Kadir, Shamsiah; Abu Hasan, Ahmad Sauffiyan (CMIWS and UiTM Press, 2014)
This study aims to analyse propaganda technique used in alternative Malaysian print media, by using the ‘Harakah’ as a case study. The two objectives of this study are to identify a) the types of propaganda that are in use by Harakah to influence its readers and b) the techniques of propaganda employed by Harakah to influence its readers. Qualitative media content analysis is conducted in this study; a specialised sub-set of content analysis as well as being a wellestablished research methodology. Data collected is analysed to determine the frequent types and techniques of propaganda used in Harakah. Data collected are derived from the National Section of Harakah within the limits of a threemonth period from February 2013 until April 2013.